1984
DOI: 10.1159/000166812
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes in Regularly Dialyzed Patients with Chronic Renal Failure

Abstract: The prevalence of circulating immune complexes (CIC) was investigated using the Clq binding assay (Clq BA) and the conglutinin binding assay (Kg BA) in 200 patients undergoing maintenance hemodialysis. Increased C1 q binding was found in 45 % (87 of 194) of the patients, and the modified Kg BA gave elevated values in 31 % (20 of 65). The prevalence of CIC was similar in American and Swiss patients, and in patients undergoing hemodialysis, self-dialysis or peritoneal dialysis. In patients with ‘nonimmunologicaΓ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…A recent study reported that the presence of C1C in regularly dialyzed patients was associated with prolonged graft survival in renal transplantation [1], We think that this new, sensitive im munoassay would be useful for detection of C1C, parti cularly intermediate C1C.…”
Section: Dear Sirmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent study reported that the presence of C1C in regularly dialyzed patients was associated with prolonged graft survival in renal transplantation [1], We think that this new, sensitive im munoassay would be useful for detection of C1C, parti cularly intermediate C1C.…”
Section: Dear Sirmentioning
confidence: 90%
“…Until now, some researchers have reported that CIC were detected with a high incidence in patients on main tenance hemodialysis [1] and glomerulonephritis [2], by the method of the Raji cell radioimmunoassay [3], the radiolabeled Clq binding assay [4], or the microcomple ment consumption test [5]. These indirect assays are based on the immunochemical properties of immune complexes, and each has its special reactivity and sensi tivity.…”
Section: Dear Sirmentioning
confidence: 99%
“…Several studies have demonstrated the high preval ence of circulating IC in patients on maintenance hemo dialysis [18][19][20][21]. This might be partially due to the expo sure of these patients to several antigenic stimuli, includ ing infections, drugs, and agents that are formed in the circulation through the extracorporeal circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that circulating IC are detected with a high incidence in patients on hemodialysis [18][19][20][21], and that the presence of 1C in dialyzed patients is associated with prolonged graft survival in renal transplantation [19].…”
Section: Introductionmentioning
confidence: 99%
“…About 30% of patients are positive for anticardiolipin antibodies [16, 17]. This raises the possibility of some abnormal antigenic stimulation or exposure to nuclear superantigens leading to this erratic inflammatory response seen in NSF, but then the patients who developed NSF have never been studied for the presence of the antigens or antiphospholipid antibodies.…”
Section: Etiologymentioning
confidence: 99%